Microbial community dynamics and their relationships with organic and metal pollutants of sugarcane molasses-based distillery wastewater sludge. (1st January 2022) - Tripathi, Sonam; Purchase, Diane; Al-Rashed, Sarah; Chandra, Ram
Abstract: Distillery sludge is a major source of aquatic pollution, but little is known about their microbial community and their association with the organic and metal pollutants. Sugarcane molasses-based distillery is an important industry in India, although the waste is usually treated prior to disposal, the treatment is often inadequate. The adverse effects of the organic and metal pollutants in sugarcane molasses-based distillery sludge on the microbial biodiversity and abundance in the disposal site have not been elucidated. This study aims to address this gap of knowledge. Samples were collected from the discharge point, 1 and 2 km downstream (D1, D2, and D3, respectively) of a sugarcane distillery in Uttar Pradesh, India, and their physico-chemical properties characterised. Using QIIME, taxonomic assignment for the V3 and V4 hypervariable regions of 16 S rRNA was performed. The phyla Proteobacteria (28–39%), Firmicutes (20–28%), Bacteriodetes (9–10%), Actinobacteria (5–10%), Tenericutes (1–9%) and Patescibacteria (2%) were the predominant bacteria in all three sites. Euryechaeota, were detected in sites D1 and D2 (1–2%) but absent in D3. Spirochaetes (5%), Sinergistetes (2%) and Cloacimonetes (1%) were only detected in samples from site D1. Shannon, Simpson, Chao1, and Observed-species indices indicated that site D1 (10.18, 0.0013, 36706.55 and 45653.84, respectively) has higher bacterial diversity and richness than D2 (6.66, 0.0001, 25987.71 and 49655.89, respectively) and D3 (8.31, 0.002, 30345.53 and 30654.88, respectively), suggesting the organic and metal pollutants provided the stressors to favour the survival of microbial community that can biodegrade and detoxify them in the distillery sludge. This study confirmed that the treatment of the distillery waste was not sufficiently effective and provided new metagenomic information on its impact on the surrounding microbial community. It also offered new insights into potential bioremediation candidates. Graphical abstract: Image 1 Highlights: First report of bacterial community and profile in sugarcane distillery sludge. Proteobacteria (28–39%), Firmicutes (20–28%) & Actinobacteria (5–10%) detected. Organic and metal pollutants exerted selective pressure on microbial community. Highest diversity ( H' >10) and richness (Chao1>36706) in the most polluted site. Bacterial community could provide candidates for sustainable remediation.